2007
DOI: 10.1016/j.trstmh.2006.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Serological screening and toxoplasmosis exposure factors among pregnant women in the Democratic Republic of Sao Tome and Principe

Abstract: The seroprevalence of Toxoplasma gondii infection among pregnant women in the Democratic Republic of Sao Tome and Principe (DRSTP) from November 2003 to March 2004 was determined by detection of serum anti-T. gondii antibodies. A short questionnaire interview for pregnant women was performed to investigate risk factors associated with T. gondii infection, including consumption of raw meat or unwashed vegetables, drinking unboiled water and keeping pets (cats and dogs). The overall seroprevalence of T. gondii i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 20 publications
5
22
0
3
Order By: Relevance
“…Water has been implicated as a source of Toxoplasma infection and has been reported globally for pregnant women. 28,30,[37][38][39][40] On the basis of these findings, serial screening for Toxoplasma infection in the first, second, and third trimesters might make it feasible to detect when seroconversion occurs, particularly among high-risk pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Water has been implicated as a source of Toxoplasma infection and has been reported globally for pregnant women. 28,30,[37][38][39][40] On the basis of these findings, serial screening for Toxoplasma infection in the first, second, and third trimesters might make it feasible to detect when seroconversion occurs, particularly among high-risk pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, the reported seroprevalence was 17.3z in the United Kingdom (9), 31.7z in Upper Austria (10), 43.8z in France (11), 4z in South Korea (12), and 10.3z in Japan (13). In developing countries, 6.1z to 20.0z of pregnant women in Mexico had antiToxoplasma IgG antibodies (14), 49.5z in Brazil (15), 10.6z in Changchun, northern China (16), 28.3z in southern Thailand (17), and 75.2z in Sao Tome and Principe, West Africa (18).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies regarding toxoplasmosis in pregnancy in Brazil [18,19] and other countries [20-28], try to estimate the prevalence of the disease or infection and its determinant factors. As an example, we cite a study with 425 pregnant girls who were receiving prenatal care in basic health care units in the city of Pelotas, Rio Grande do Sul, Brazil which identified that 65% of the pregnant girls did not know about the disease, while most associated it with having cats as pets and less than one third of them associated it with the handling and the consumption of undercooked raw meats and raw vegetables [29].…”
Section: Introductionmentioning
confidence: 99%